Stem and progenitor cells for liver repopulation: can we standardise the process from bench to bedside?. Issue 4 (17th December 2008) - Sancho-Bru, P; Najimi, M; Caruso, M; Pauwelyn, K; Cantz, T; Forbes, S; Roskams, T; Ott, M; Gehling, U; Sokal, E; Verfaillie, C M; Muraca, M
Abstract : There has been recent progress in the isolation and characterisation of stem/progenitor cells that may differentiate towards the hepatic lineage. This has raised expectations that therapy of genetic or acquired liver disease might be possible by transplanting stem/progenitor cells or their liver-committed progeny. However, it is currently impossible to determine from the many documented studies which of the stem/progenitor cell populations are the best for therapy of a given disease. This is largely because of the great variability in methods used to characterise cells and their differentiation ability, variability in transplantation models and inconsistent methods to determine the effect of cell grafting in vivo. This manuscript represents a first proposal, created by a group of investigators ranging from basic biologists to clinical hepatologists. It aims to define standardised methods to assess stem/progenitor cells or their hepatic lineage-committed progeny that could be used for cell therapy in liver disease. Furthermore standardisation is suggested both for preclinical animal models to evaluate the ability of such cells to repopulate the liver functionally, and for the ongoing clinical trials using mature hepatocytes. Only when these measures have been put in place will the promise of stem/progenitor-derived hepatocyte-based therapies become reality.